IMPROVEMENT OF THE WORKING SYSTEM IN MR. WASH LAUNDRY USING ERGONOMIC PARTICIPATORY METHOD - Rini, Asih Setyo; Prakoso, Indro (Journal of Industrial Engineering Management, 2021)
Mr. Wash laundry is one of the Small and Medium Enterprises (SME) located in Yogyakarta. This business was founded in 2015 with 2 workers. In work operations, many involve physical activities that can cause fatigue and musculoskeletal complaints, causing decreased productivity and miscommunication to consumers. Therefore, this research was conducted to improve the work system to minimize these impacts. The method in this study uses an ergonomics participator. This method involves a participatory team, namely ergonomists, owners, and workers. The result of this research is the design of an ironing table and chair using the anthropometric specifications of workers which can reduce fatigue and musculoskeletal complaints.